The impact of tuition fees and support on university participation in the UK - Lorraine Dearden; Emla Fitzsimons; Gill Wyness (Institute for Fiscal Studies (IFS), 2011)
Understanding how policy can affect university participation is important for understanding how governments can promote human capital accumulation. In this paper, we estimate the separate impacts of tuition fees and maintenance grants on the decision to enter university in the UK. We use Labour Force Survey data covering 1992-2007, a period of important variation in higher education finance, which saw the introduction of up-front tuition fees and the abolition of maintenance grants in 1998, followed some eight years later by a shift to higher deferred fees and the reinstatement of maintenance grants. We create a pseudo-panel of university participation of cohorts defined by sex, region of residence and family background, and estimate a number of different specifications on these aggregated data. Our findings show that tuition fees have had a significant negative effect on participation, with a 1,000 increase in fees resulting in a decrease in participation of 3.9 percentage points, which equates to an elasticity of -0.14. Non-repayable support in the form of maintenance grants has had a positive effect on participation, with a 1,000 increase in grants resulting in a 2.6 percentage point increase in participation, which equates to an elasticity of 0.18. These findings are comparable to, but of a slightly lower magnitude than, those in the related US literature.
Keywords: I21; I22; I28; 330; university participation; higher education funding policies; tuition fees; maintenance grants; pseudo-panel; Bildungspolitik; Humankapital; Bildungsverhalten; Studienfinanzierung; Subvention; Hochschule; Großbritannien